Quality management in the tourism industry - Katanić Zoran; Todosijević-Lazović Snežana; Todosijević Radmilo (Mining and Metallurgy Engineering Bor, 2017)
The traditional approach to the management in the function of quality the tourist industry has not offered the high quality product or service. Namely, dissatisfaction is a response to the managerial approach, reduced customer satisfaction, and small profit. This work points out to a continued access to the quality, necessity of total quality management, levels of TQM implementation and benchmarking. Furthermore, it analyzes the monitoring of quality control to be allocated and coordinated in the organization.